TEKNIK KLOWONG DALAM UPAYA PENGEMBANGAN MODEL PEWARISAN TRADISI MEMBATIK WARGA RIFA'IYAH DI DESA KALIPUCANG WETAN, JAWA TENGAH - Prizilla, Aquamila Bulan; Sachari, Agus (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
Batik Rifa’iyah is a batik created and developed by followers of Shaikh Ahmad Rifa’i, also known as the Rifa’iyah. The tradition stemmed from Shaikh Ahmad Rifa’i's prohibition of drawing living beings. Today, the Batik making tradition is in decline, and would go extinct without proper preservation efforts. One way to preserve the tradition is by passing the Rifa’iyah batik making tradition to the next generation of the community. This study is limited to the next generation of Rifa’iyah community in Kalipucan Wetan whose age between 15-30 years old. This study focuses on one of batik making technique called the klowong. The study’s methodology is adopted from ethnographic approaches. The approach analyzes socio-cultural aspects, of which are experimented and applied by using the klowong technique to pass down the batik making tradition to Rifa’iyah in Kalipucang Wetan. Qualitative methods used are literature studies, field study by observation, in-depth interviews, voice recordings, and photography. Currently, the klowong technique is passed down by imitation. Preservation of the klowong technique requires innovation to help apprentices learn the technique. It is found different models of passing down the klowong technique are required to suit a batik maker’s skills.